HUBUNGAN KONJUNGTIF DALAM PENERJEMAHAN - - Sriyono (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2012)
A text should have  a unity in order to represent its cohesiveness. One of the aspects in determining the unity is logical markers. Conjunctive Relation has a significant role in determining logical relation in a text. As logical markers, it unavoidably enables translators to configure logical meaning both in source text and in target text when translators are doing translation activity. In addition, conjunctive relation occasionally appears in several forms in either source text or target text. The  forms of conjunctive relation can be realized explicitly or metaphorically signaling logical relation.